PENGARUH PENDEKATAN REALISTIC MATHEMATIS EDUCATION (RME) TERHADAP KEMAMPUAN PENALARAN MATEMATIS DAN MOTIVASI SISWA MTs BIRRUL WALIDAIN RENSING - RODY SATRIAWAN; ABDULLAH ABDULLAH; NILA HAYATI; RISTU HAIBAN HIRZI; EKA OKTAVIANI (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2023)
This study aims to determine the effect of a realistic mathematics education approach on mathematical reasoning and learning motivation of 8-th graders in the 2021/2022 academic year. This type of research is a quasie experimental research with the non-equivalent posttest control group design. The population and sample of this study used all VIII grade students at MTs. Birrul Walidain NW Rensing determined by using a saturated sampling technique. The data collection technique used a descriptive test to measure students’ mathematical reasoning abilities and a questionnaire to measure students’ learning motivation. To test the data analysis , the data normality test was carried out with lilifors, the data coss-line test was carried out with the F test. While the hypothesis testing technique used was simple regression analysis. Based on the results of hypothesis testing tcount = 4,130 and ttable = 2,101. Because tcount > ttabel (4,130 > 2,101) at a significant level of 5%, it can be concluded that the null hypothesis test is rejected and the alternative hypothesis is accepted, which means that there is a positive effect of using the Realistic Mathematics Education (RME) approach on mathematical reasoning and student motivation. The results of data analysis obtained from the value of the determinant of e simple corerrelation of 0,461 which means that the magnitude of the effect of using the Realistic Mathematics Education (RME) approach on mathematical reasoning and student motivation is 46,1%. ABSTRAKPenelitian ini bertujuan untuk mengetahui ada tidaknya pengaruh yang positif antara pembelajaran pembelajaran dengan pendekatan realistic mathematics education (RME) yang positif terhadap kemampuan penalaran matematis siswa kelas VIII MTs Birrul Walidain NW Rensing tahun pelajaran 2021/2022. Jenis penelitian ini adalah penelitian eksperimen semu (quasi experimental). Desain penelitian yang digunakan adalah non-equivalent posttest control group design. Populasi dalam penelitian ini meliputi semua siswa kelas VIII MTs. Birrul Walidain NW Rensing. Sampel dalam penelitian ini diambil siswa kelas VIII.A dan VIII.B. Teknik analisis data menggunakan analisis regresi sederhana. Teknik pengumpulan data yang digunakan yaitu tes dan non-tes. Hasil penelitian menunjukkan bahwa (1) terdapat pengaruh pembelajaran dengan pendekatan realistic mathematics education (RME) yang positif dan signifikan terhadap kemampuan penalaran matematis siswa kelas VIII MTs. Birrul Walidain NW Rensing tahun pelajaran 2021/2022; dan (2) terdapat pengaruh pembelajaran dengan pendekatan realistic mathematics education (RME) yang positif dan signifikan terhadap motivasi siswa kelas VIII MTs. Birrul Walidain NW Rensing tahun pelajaran 2021/2022.